Database Analysis of Eplerenone Use in Japanese Hypertensive Patients in Clinical Practice. (3rd March 2019) - Takahashi, Shoko; Ii, Yoichi; Yamamoto, Yuji; Ikeda, Aya; Fujimoto, Yoko
Abstract : Eplerenone, a mineralocorticoid receptor antagonist (MRA), is available in Japan, but details of its use in clinical settings have not been thoroughly investigated. Thus, this study was aimed at examining the characteristics of eplerenone-prescribed hypertensive patients in Japan, describing the combination patterns of antihypertensive medications, and comparing eplerenone's mean doses with respect to concomitant diseases. Data of 160, 992 hypertensive patients who used the same drugs for six months or more were collected from an insurance database from January 1, 2009, to December 31, 2013. The number of MRA-receiving patients among the extracted population was 3, 274 (2%). Compared to patients on eplerenone or spironolactone, patients on neither drug had fewer comorbidities. Eplerenone was administered in combination with calcium channel blockers and angiotensin II receptor blockers in 23.1% and as monotherapy in 6.6% of cases. The most frequent initial daily dose of eplerenone was 50 mg/day followed by 25 mg/day irrespective of the presence of a comorbidity. MRA use was as low as 2%, but its use was more frequent in patients with comorbidities compared to that of other antihypertensives. Despite studies showing eplerenone's efficacy and safety in high-risk hypertensive patients with albuminuria, the drug is not widely used.